2021
DOI: 10.3390/life11060569
|View full text |Cite
|
Sign up to set email alerts
|

Gender Difference in Architectural and Mechanical Properties of Medial Gastrocnemius–Achilles Tendon Unit In Vivo

Abstract: This study aims to explore whether gender differences exist in the architectural and mechanical properties of the medial gastrocnemius–Achilles tendon unit (gMTU) in vivo. Thirty-six healthy male and female adults without training experience and regular exercise habits were recruited. The architectural and mechanical properties of the gMTU were measured via an ultrasonography system and MyotonPRO, respectively. Independent t-tests were utilized to quantify the gender difference in the architectural and mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
3
2
0
Order By: Relevance
“…We think that the BB and BF viscoelastic properties are affected by sex to a greater extent in males than females. Our results are consistent with those of other studies that reported higher gastrocnemius stiffness and lower elasticity in males than in females [36,37].…”
Section: Discussionsupporting
confidence: 94%
“…We think that the BB and BF viscoelastic properties are affected by sex to a greater extent in males than females. Our results are consistent with those of other studies that reported higher gastrocnemius stiffness and lower elasticity in males than in females [36,37].…”
Section: Discussionsupporting
confidence: 94%
“…FL is influenced by factors such as tendon length, joint structure, limb proportions, and age 20 22 . Our study also highlighted sex differences in VL, GM, and GL regarding PA (i.e., males > females), which is also in line with the literature 17 , 23 , 24 . Males are taller than females, which has been genetically explained elsewhere 25 , 26 , so could that alone explain the differences in muscle architecture?…”
Section: Discussionsupporting
confidence: 92%
“…Our study (Figures 3, 4) and previous studies reported MDCs for PT and AT stiffness and length measurements using the myotonometry method (12,13,15) and the EFOV-US technique (19,20), respectively. With regard to the results of previous studies investigating changes in PT and AT stiffness (31,(48)(49)(50)(51)(52)(53) and length (34, 36-38, 43, 44, 54) in sports and medicine, these changes could be detected outside the measurement error using myotonometry and the EFOV-US technique, which supports the practical applicability of both technologies. For future studies using the EFOV-US technique, and as conducted here, we recommend the usage of a fixable brace to avoid axial shifts of the US probe.…”
Section: Clinical and Practical Implicationssupporting
confidence: 65%